THE SAFETY OF STATINS: WHAT A PHYSICIAN NEEDS TO KNOW - D. A. Napalkov (Столичная издательская компания, 2015)
Various aspects of the safety of statins in clinical practice are discussed: hepatotoxicity, myopathy and rhabdomyolysis, the impact on the diabetes and cognitive dysfunction onset, renal function impairment.